Assessing the moderating role of technological innovation on food security in poverty reduction within the Visegrad region - Kwabena Nsiah Takyi; Beata Gavurova; Martin Mikeska (Discover Sustainability)
Abstract The global shift for sustainable development has elicited nations and governments to develop policies to safeguard humankind and the environment. The investigation premised on the poverty reduction within the Visegrad communities (Czech Republic, Hungary, Poland, and Slovakia). The evaluation employed panel data from 2000 to 2022 on the variables of poverty (POV), food security (FOD), foreign direct investment inflow (FDI), economic progress (ECP), population growth (POG), inflation growth (ING), and technological innovation (TIN). Various preliminary assessment of cross-sectional dependence, unit root, and cointegration was evaluated to ensure data reliability and validity. The econometric approach of Cross-Sectional Augmented Distributed Lag (CS-ARDL) model was adopted to study the short- and long-term affiliation. The findings revealed that (a) FOD, FDI, POG, and TIN had a material influence on poverty reduction. (b) However, ECP and ING appreciation poverty rate within the Visegrad region. (c) Again, there was a serial moderating effect of TIN on the affiliation between FOD and POV in the Visegrad region. Furthermore, the Dumitrescu-Hurlin causality test indicated a unidirectional nexus between FOD, FDI, POG, and TIN with POV reduction. While a bidirectional was established on ECP and ING with POV reduction. The outcome serves as a policy and practical supplement to government and institutional agencies in charge of poverty mitigation. The outcome recommend that government should invest in technological innovation to improve food security and poverty reduction to achieve the SDG1 by 2030.